Freezing of ridges and water networks preserves the Gamburtsev Subglacial Mountains for millions of years. Issue 22 (17th November 2014) - Creyts, Timothy T.; Ferraccioli, Fausto; Bell, Robin E.; Wolovick, Michael; Corr, Hugh; Rose, Kathryn C.; Frearson, Nicholas; Damaske, Detlef; Jordan, Tom; Braaten, David; Finn, Carol
Abstract Once an ice sheet grows beyond a critical thickness, the basal thermal regime favors melting and development of subglacial water networks. Subglacial water is necessary for bedrock erosion, but the exact mechanisms that lead to preservation of subglacial topography are unclear. Here we resolve the freezing mechanisms that lead to long‐term, high‐altitude preservation across the Gamburtsev Subglacial Mountains in East Antarctica. Analyses of a comprehensive geophysical data set reveal a large‐scale water network along valley floors. The ice sheet often drives subglacial water up steep topography where it freezes along high ridges beneath thinner ice. Statistical tests of hypsometry show the Gamburtsevs resemble younger midlatitude mountains, indicating exceptional preservation. We conclude that the Gamburtsevs have been shielded from erosion since the latest Eocene (∼34 Ma). These freezing mechanisms likely account for the spatial and temporal patterns of erosion and preservation seen in other glaciated mountain ranges.